2002
DOI: 10.1109/tsmcb.2002.999810
|View full text |Cite
|
Sign up to set email alerts
|

Assigning cells to switches in cellular mobile networks using taboo search

Abstract: The design of wireless telecommunications networks is a complex process, which requires solving simultaneously many difficult combinatorial optimization problems. We propose a taboo-search approach dedicated to one of the aforementioned design optimization problems, namely the cell assignment problem. Our approach defines a series of moves applicable to an initial solution in order to improve the cost and establish the feasibility of the solution. For this purpose, we identify a gain structure with update proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…The values of l i , M k and the positions of the cells and switches for this problem are given in Tables 3 and 4. Note that the trend is to assign as many cells as possible 3 to the nearest switch (switch 2 in this case). Cells in the center of the network, which have more probability of handoff than other cells, are always assigned to the same switch.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The values of l i , M k and the positions of the cells and switches for this problem are given in Tables 3 and 4. Note that the trend is to assign as many cells as possible 3 to the nearest switch (switch 2 in this case). Cells in the center of the network, which have more probability of handoff than other cells, are always assigned to the same switch.…”
Section: Resultsmentioning
confidence: 99%
“…In [3], Pierre and Houéto discussed an approach based on TS. In this paper the authors showed that their TS approach outperforms a simulated annealing (SA) approach for the CTSAP.…”
Section: Previous Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been successfully used for various system-level design problems, such as yield maximization problems [Alippi et al 2003], FIR filter design [Traferro et al 1999], mapping and scheduling of task graphs on SoCs [Wild et al 2003], and latency-area tradeoffs for NoCs [Cardoso et al 2005]. Several researchers have compared tabu search with other optimization heuristics, such as simulated annealing and genetic algorithms and shown the superiority of tabu search with regard to optimization time and quality of results [Hajji et al 2002;Wild et al 2003;Pierre and Houeto 2002;Krishnamachari and Wicker 2000;Eles et al 1997].…”
Section: The Tabu Search Based Heuristicmentioning
confidence: 99%